قبول خبر الآحاد فيما تعم به البلوى: دراسة أصولية تطبيقية - تبيدي، بابكر الخضر يعقوب (جامعة أم درمان الإسلامية - معهد البحوث والدراسات الإستراتيجية, 2022)
يناقش هذا البحث قبول خبر الآحاد فيما تعم به البلوى، والخلاف فيه بين الجمهور والحنفية، وجاء هذا البحث ليجلي هذه المسألة المهمة ويبرز أهم تطبيقاتها. وسرت في كتابة هذا البحث على خطة: مقدمة، وأربعة مباحث، وخاتمة. أما المقدمة فقد تناولت فيها موضوع البحث وبينت أهميته وسبب اختياره. أما المبحث الأول فكان في التعريف بأهم مفردات عنوان البحث. والمبحث الثاني: في شروط العمل بخبر الآحاد. والمبحث الثالث: مذاهب العلماء في قبول خبر الآحاد الوارد فيما تعم به البلوى. المبحث الرابع: في نماذج من الأمثلة الفقهية التي تبين أثر الخلاف في المسألة. وخاتمة تضمنت أهم النتائج التي خلص إليها البحث. This research discusses the acceptance of the news of Sundays as pervasive in the trial, and the disagreement in it between the public and the tap, and this research came to clarify this important issue and highlight its most important applications. I proceeded in writing this research according to a plan consisting of: an introduction, four chapters, and a conclusion. As for the introduction, it dealt with the topic of the research and indicated its importance and the reason for choosing it. The first topic was in the definition of the most important vocabulary of the title of the research. And the second topic: The second topic: the conditions for working with the news of Sundays. The third topic: the doctrines of scholars regarding the acceptance of the news of the reported in what is prevalent in the affliction. Fourth topic: Examples of jurisprudential examples that show the impact of the dispute on the issue. And a conclusion that included the most important findings of the research.
Keywords: المسائل الفقهية -- أصول الأحكام -- أخبار الآحاد -- أحكام الصلاة -- المذاهب الفقهية